Study on the mechanism of lupenone for treating type 2 diabetes by integrating pharmacological evaluation and network pharmacology - Feng Xu; Mei Zhang; Hongmei Wu; Yuanmin Wang; Ye Yang; Xiangpei Wang (Taylor & Francis Group, 2022)
Context Lupenone (LUP) is the active ingredient of Musa basjoo Sieb. et Zucc. (Musaceae) with antidiabetes effects, but an unclear underlying mechanism of action.Objective Animal experiments combined with network pharmacology were used to explore the mechanism of LUP for treating diabetes.Materials and methods Insulin resistance (IR) in male Sprague-Dawley rats with type 2 diabetic was induced using a high-fat diet and streptozotocin. The selected rats were divided into normal group, model group, positive group and LUP (2.0, 4.0 and 8.0 mg/kg) groups, and orally administrated twice daily with Tween 80, rosiglitazone or LUP. Fasting blood glucose (FBG), oxidative stress index, blood lipids and IR-related targets were detected. A network pharmacology analysis was performed.Results Compared to the model group, LUP (8.0 mg/kg) significantly decreased the levels of FBG (22.3%), LEP (9.5%), HbA1c (14.9%) and MDA (12.3%), increased the ADPN (24.2%) levels and GSH-PX activity (12.4%) (p < 0.05), improved oxidative stress, lipid metabolism disorders and pancreas pathological changes, increased the mRNA and protein expression of InsR (3.7-fold and 1.3-fold), IRS-1 (3-fold and 2-fold), IRS-2 (2-fold and 1.6-fold), GLUT-4 (2-fold and 2.4-fold) in skeletal muscle and IRS-1 (6-fold and 1.6-fold), IRS-2 (5.8-fold and 1.5-fold), GLUT-4 (2.5-fold and 1.7-fold) and PPAR-γ (7-fold and 1.4-fold) in adipose tissue (p < 0.05). Network pharmacology analysis revealed that LUP improves IR by multiple targets and signal pathways.Conclusions The mechanism of LUP for treating diabetes is related to improving IR. LUP has the potential to be developed as a new drug for treating type 2 diabetes.